Sosialisasi Pemanfaatan Google Form Sebagai Media Pembelajaran Berbasis Digital Bagi Guru Methodis Pematangsiantar - Siregar, Nur Hamida; Hutabarat, Purnama Helena (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2024)
Information technology is currently experiencing very rapid development and affects all areas of life. One of them is the field of education. The world of education and especially teachers must be able to keep up with technological developments in order to create innovative and enjoyable learning processes and be able to maximize the use of technology in evaluating learning outcomes. The problem is that many teachers still have difficulty implementing the use of Google Forms as a digital learning medium and a medium for evaluating learning outcomes. Socialization activities are carried out with the aim of introducing, training, and teaching the maximum use of Google Forms. Activities are carried out with direct practice in making Google forms according to the teaching materials in each teacher's field of study. Practical activities are monitored and guided directly by resource persons and fellow lecturers. The socialization activities went well, as shown by the enthusiasm of the teachers in participating in the training and the teachers' activeness in the process of asking questions related to socialization. It is hoped that this outreach can help Methodist teachers develop more creative and innovative digital learning media by utilizing Google Forms.